Pemberdayaan Masyarakat Terhadap Pendampingan Belajar Matematika Anak di Desa Batu Malenggang Kabuapten Langkat - Muhammad Arif Hidayat; Sofia Rahmi (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
This community empowerment activity is a breakthrough for math teachers and students who wish to share their math knowledge with small community organizations. This form of community empowerment is used to support and help the community implement mathematics teaching for children; help children with disabilities understand math; insights from DKM management and staff (Mushola Musyawarah Kemakmuran) on learning math fun for children; and develop familiarity and awareness. The DKM served as an impetus to integrate the da'wah program with the needs of the congregation in the education of children, especially in mathematics. The partner of this activity is the Musholla Prosperity Council, a non-profit organization committed to supporting the well-being and empowerment of mosques. In this case, parents who are members of the prayer hall church often find it difficult to guide their sons / daughters in their studies, especially in math due to their limited math skills. This activity aims to improve the understanding of managers and executives at DKM about fun math learning for kids by combining learning with math games and teaching aids. This activity in the process is very helpful in increasing interest in learning math for students and parents in Batu Malenggang Village, Langkat Regency. Keywords: Children, Parents, DKM, Mathematics, Learn